Forecasting the Milk Prices from a Supply Chain Management Perspective in the Northern Kazakhstan - Talgat A. Kussaiynov; Zhazira O. Zhakupova (International Journal of Supply Chain Management, 2019)
Abstract-The primary goal of supply chain management is to meet customer needs through the most efficient use of resources, including the allocation of capacity, inventory and workforce. In theory, the supply chain management seeks to match supply and demand and seeks to do so at minimal cost. And the main indicator of changes in the ratio of supply and demand is the change in the price of products. Trend-seasonal time series models were used to analyze the price behavior in the milk market of the Northern region of Kazakhstan. The use of chain indexes provides models that give more reliable predictions. Calculations based on statistical data on average monthly prices for milk sold by farms of Kostanay region in the period from 2010 to 2018. Seasonal ups and downs in the dynamics of prices for milk were estimated in the model using dummy variables. Validation of the model was carried out as follows: the initial set of data was divided into two subsets – one for estimating the parameters of the equation, the other – for its validation. With use of the data from the first subset, the parameters of the equation were estimated. Then the data from the second subset were inserted into the equation to get predicted values of the response variable. Finally, the predicted values of the indicator were compared with the corresponding known values from the second subset. The degree of deviation of milk prices calculated on the basis of the index model from the actual prices, estimated as the ratio of the standard error to the average actual value of the indicator, doesnot exceed 3%.Price forecasting based on chain indexes falls within the framework of Bayesian approach. The model of chain price indexes can be used by farms for the effective organization of production and sale processes, taking into account the seasonal characteristics in the behavior of the market.